2011
DOI: 10.1089/aid.2010.0252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Personal Lubricants That Can Cause Rectal Epithelial Cell Damage and Enhance HIV Type 1 Replicationin Vitro

Abstract: Over-the-counter personal lubricants are used frequently during vaginal and anal intercourse, but they have not been extensively tested for biological effects that might influence HIV transmission. We evaluated the in vitro toxicity anti-HIV-1 activity and osmolality of popular lubricants. A total of 41 lubricants were examined and compared to Gynol II and Carraguard as positive and negative controls for toxicity, respectively. Cytotoxicity was assessed using the XTT assay. The MAGI assay with R5 and X4 HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 16 publications
4
64
0
Order By: Relevance
“…The assay was performed as previously described (9), except that the medium was replaced on the day of the assay with fresh Dulbecco's modified Eagle's medium (DMEM) without phenol red (Invitrogen, Grand Island, NY) and supplemented with MITOϩ Serum Extender (BD Biosciences). All formulations were diluted 1:10 in the media described above, and 300 l was applied in triplicate in the upper chambers.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as previously described (9), except that the medium was replaced on the day of the assay with fresh Dulbecco's modified Eagle's medium (DMEM) without phenol red (Invitrogen, Grand Island, NY) and supplemented with MITOϩ Serum Extender (BD Biosciences). All formulations were diluted 1:10 in the media described above, and 300 l was applied in triplicate in the upper chambers.…”
Section: Methodsmentioning
confidence: 99%
“…25 Despite the enhanced comfort and pleasure lubricants afford, recent literature has highlighted the enhanced risk they may also confer. 22 Laboratory research has shown that many of these agents compromise the integrity of the epithelial lining of the rectum and colon, which could increases susceptibility to infection, 20,21,24,39 and that several products even amplify HIV replication in vitro. 20 Notably, research to date exploring lubricant as a mechanism of HIV/STI transmission has largely focused on PAI risk as it pertains to the receptive partner, and it is therefore unknown whether lubricants enhance susceptibility of the insertive partner's penis to infection.…”
Section: Calabrese Et Almentioning
confidence: 99%
“…22 Laboratory research has shown that many of these agents compromise the integrity of the epithelial lining of the rectum and colon, which could increases susceptibility to infection, 20,21,24,39 and that several products even amplify HIV replication in vitro. 20 Notably, research to date exploring lubricant as a mechanism of HIV/STI transmission has largely focused on PAI risk as it pertains to the receptive partner, and it is therefore unknown whether lubricants enhance susceptibility of the insertive partner's penis to infection. Moreover, it is conceivable that by reducing friction between the penis and anus, lubricants may decrease the likelihood of the receptive partner experiencing anal tearing or bleeding, potentially reducing exposure of the insertive partner to blood-borne pathogens (e.g., HIV).…”
Section: Calabrese Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent metaanalysis demonstrated that the estimated per-act human immunodeficiency (HIV) transmission risk (per 10,000 exposures) for RAI is 138, compared to 11, 8, and 4 for insertive anal intercourse, receptive penile-vaginal intercourse, and insertive penile-vaginal intercourse, respectively (10). The risk of HIV acquisition via unprotected RAI may be further exacerbated through the improper use of vaginal microbicide gels or high osmolality personal lubricants in the rectal compartment, which have been shown to cause cellular inflammation and epithelial damage (11)(12)(13)(14)(15)(16)(17)(18)(19). These studies collectively highlight a need for a microbicide formulation that is specifically designed for safe application in both the vaginal and rectal compartments and that may also serve as a lubricant.…”
mentioning
confidence: 99%